Tinjauan Biblika Pelayanan Profetik Bagi Masa Kini - Yohanes, Heppy (Pusat Studi Pentakosta Indonesia, 2022)
The prophetic ministry is still a hotly discussed issue. The form of prophetic ministry still raises various questions, debates, and contradictions. Prophetic training for Christians with Pentecostal or Charismatic denominations has sprung up in various countries with the aim of awakening people to prophetic ministry. Various questions regarding this matter also arise, such as what is prophetic ministry and how is prophetic ministry? To obtain information about biblical prophetic services and to answer these two questions, this research was conducted qualitatively descriptively with literature study. This study describes aspects of prophetic service and also the form of prophetic service. Prophetic ministers are certainly people who receive a special call and are given special gifts in prophetic ministry. The most important prophetic ministry is to convey the voice of God that is edifying, exhorting, and comforting. The voice of God can also take the form of a vision. The voice of God in prophetic ministry can also be a prediction of what will happen in the future. The gift that God gave to accompany the prophetic ministry can be seen from the ministry for healing and miracles. Prophetic ministry has the main goal of making a person walk and live according to God's Word.Pelayanan profetik masih merupakan sebuah isu yang hangat dibahas. Bentuk pelayanan profetik masih menimbulkan berbagai pertanyaan, perdebatan, dan pertentangan. Pelatihan profetik pada kalangan Kristen berdenominasi Pentakosta atau Kharismatik bermunculan di berbagai negara dengan tujuan untuk membangkitkan orang terhadap pelayanan profetik. Berbagai pertanyaan mengenai hal ini pun timbul, seperti apakah pelayanan profetik itu dan bagaimanakah pelayanan profetik itu? Untuk mendapatkan informasi mengenai pelayanan profetik yang alkitabiah dan untuk menjawab kedua pertanyaan tersebut, maka penelitian ini dilakukan secara kualitatif deskriptif dengan studi kepustakaan. Penelitian ini memaparkan aspek dalam pelayanan profetik dan juga bentuk dari pelayanan profetik. Para pelayan profetik pastinya merupakan orang yang menerima panggilan secara khusus dan diberikan karunia khusus dalam melayani profetik. Pelayanan profetik yang paling utama adalah menyampaikan suara Tuhan yang bersifat membangun, menasihati, dan menghibur. Suara Tuhan tersebut juga dapat berbentuk penglihatan. Suara Tuhan pada pelayanan profetik juga bisa berupa ramalan tentang apa yang akan terjadi di masa depan. Karunia yang Tuhan berikan untuk menyertai pelayanan profetik terlihat dari pelayanan untuk kesembuhan dan mujizat. Pelayanan profetik memiliki tujuan utama untuk membuat seseorang dapat berjalan dan hidup sesuai dengan Firman Tuhan.